Hamlet - Shakespeare, William, 1564-1616 (Salt Lake City, UT : Project Gutenberg, 1999)
"Hamlet" by William Shakespeare is a tragedy written between 1599 and 1601. Set in Denmark, the play follows Prince Hamlet as he seeks revenge against his uncle Claudius, who murdered Hamlet's father to seize the throne and marry the queen. When a ghost reveals the truth of his father's death, Hamlet vows vengeance but struggles with uncertainty and madness$1 (Bboth feigned and real. Widely considered one of the greatest plays ever written, this dark tale of betrayal, duty, and moral corruption remains powerfully influential. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Hamlet
There are improved editions of this title. See eBook #100 (the Complete Shakespeare) as well as #1787 (this specific play).
Release date is 1999-06-01
Keywords: Tragedies (Drama); Hamlet (Legendary character) -- Drama; Kings and rulers -- Succession -- Drama; Murder victims' families -- Drama; Fathers -- Death -- Drama; Revenge -- Drama; Princes -- Drama; Denmark -- Drama